Interest rate pass-through and bank risk-taking under negative-rate policies with tiered remuneration of central bank reserves - Basten, Christoph; Mariathasan, Mike (Journal of Financial Stability, 2023)
We identify the effects of negative rates on bank behavior using difference-in-differences identification. First, we find that going negative can interrupt not only the pass-through from policy to deposit but also to mortgage rates. To preserve their deposit franchise, banks finance negative deposit with increased mortgage spreads, the more the bigger their market power. Second, negative rates on reserves induce banks to cut some reserves without replacement and replace others with riskier assets. Together with increased mortgage spreads, balance sheet restructuring preserves profits but risk-taking increases. Third, pass-through interruption and risk-taking can be reduced through tiered remuneration.